SYNTHESIS OF NEW ALKYL-4-(4-(DIALKYLAMINO) PHENYL)-1, 6-DIMETHYL-2-OXO/THIOXO-1, 2, 3, 4-TETRAHYDROPYRIMIDINE-5-CARBOXYLATES AND THEIR ANTI-MICROBIAL AND ANTI-MYCOBACTERIAL STUDIES - YEDDULA HARANADHA REDDY; CHINTHAPARTHI RADHA RANI; BHATNAGAR IRA; GANGIREDDY CHANDRA SEKHAR REDDY; KALLURU SUBRAMANYAM REDDY (International Journal of Pharma and Bio Sciences, 2013)
A series of novelalkyl-4-(4-(dialkylamino) phenyl)-1, 6-dimethyl-2-oxo/thioxo-1, 2, 3,4-tetrahydropyrimidine-5-carboxylates (4a-r) have been synthesized by Biginelli condensation with an efficient chloroindate(III) ionic liquid under mild reaction conditions in high yields. All the chemical structures of the title compounds were confirmed by elemental analysis and spectral data analysis. The newly synthesized compounds were evaluated their anti-microbial activity against Escherichia coli, Staphylococcus aurous and Candida albicans and the in vitro anti-tuberculosis activity also evaluated against Mycobacterium tuberculosis H37Rv (MTB). Among these compounds, 4m, 4o, 4n and 4pwere found to be the potent anti-tubercular compounds with minimum inhibition concentration (MIC).In addition, comparatively other compounds these compounds are also shown efficient biological activity against bacteria as well as fungi in order of 4m>4o>4n>4p.From the results it is indicative that these analogues were found to possess a significant broad spectrum of anti-microbial and anti-tubercular potentiality.